COMPARATIVE EXEGESIS: A STUDY OF HALLEL AND KERYGMA - Finkel, Asher (Journal of Dharma, 1980)
The gospels are church books' which support and guide the religious life of the Christian community. They come to describe the ministry of Jesus, as it is recalled and experienced by the original followers. Moreover, they reveal the attitudes and the historical situation of the authors or schools who are responsible for the final compositions.' An inquiry into its canonical nature (the acceptance of the works by the worshipping community) and into its christologtcal meaning (the affective response to Jesus by the believing writer) will reveal how history and theology are closely intertwined in the gospels. Rooted in this observation, the gospels should not be consulted only for the purpose of presenting a synoptic account of the historical Jesus but more so they should be studied in connection with the history of the early church.